Determination of a New Parameter, Elevated Epiretinal Membrane, by En Face OCT as a Prognostic Factor for Pars Plana Vitrectomy and Safer Epiretinal Membrane Peeling - Mitrofanis Pavlidis; Ilias Georgalas; Norbert Körber (Journal of Ophthalmology)
Purpose. To evaluate the significance of the area of epiretinal membrane (EM) that is not in contact with the retinal structure as a preoperative parameter for safer grasping of the EM and a prognostic factor for visual improvement/outcome. Methods. This prospective observational study included 73 consecutive patients (80 eyes) who underwent pars plana vitrectomy (PPV) and EM peeling. Corrected distance visual acuity (CDVA) and central foveal thickness (CFT) were evaluated preoperatively and at 12 months postoperatively. The number of initial peeling grasps was recorded in the operation protocol. The elevated EM portion was identified by en face optical coherence tomography (OCT) and processed digitally to calculate its area. Results. Surgery was found to significantly improve CDVA and decrease CFT. CDVA improvement correlated with elevated EM, preoperative CFT, and the number of grasping attempts. Conclusion. The detection of elevated EM via en face OCT could assist safer grasping of the EM and indicate the potential for visual outcome improvement after PPV and EM peeling.